Aplikasi Kombinasi Senam Kaki Diabetes Dan Senam Diabetes Sebagai Alternatif Penurunan Kadar Gula Darah Pada Pasen Diabetes Melitus Tipe 2 - Kai, Meggy; Sari, Emilda; Rahmawati, Ida (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2025)
Based on International Diabetes Federation (IDF) data, an estimated 463 million people aged 20–79 worldwide were living with diabetes in 2019, with projections rising to 578 million by 2030 and 700 million by 2045. Indonesia ranks seventh among the ten countries with the highest number of diabetes cases, totaling 10.7 million people. Banjarbaru City is one of the regions in South Kalimantan with the highest prevalence of type 2 diabetes mellitus (DM). Inadequate management of DM can result in both acute and chronic complications, including cardiovascular disorders, peripheral neuropathy, and diabetic foot. One non-pharmacological approach to reducing blood glucose levels is through physical activity, such as the Diabetes Foot Exercise (Senam Kaki Diabetes) and Diabetes Exercise (Senam Diabetes), which aim to improve circulation, strengthen muscles, and enhance glucose metabolism. This community service project aimed to improve knowledge, skills, and self-reliance among Prolanis patients with type 2 DM in applying combined foot and diabetes exercises as an alternative method to lower blood glucose levels and prevent complications. A cross-sectional analytic observational method was applied, with the population comprising 20 Prolanis patients selected using total sampling. Initial blood glucose tests (pretest) showed that 16 participants had hyperglycemia, while 4 were within normal limits. The intervention included education on DM complications and prevention, followed by the practice of combined foot and diabetes exercises. Post-intervention (posttest) results indicated a decrease in blood glucose levels in all participants, although 50% remained in the hyperglycemia category. The targeted goal was achieved, with improvements in both blood glucose control and patient knowledge. It is recommended that healthcare workers and community health cadres continue promoting and supervising the regular practice of these exercises to maintain quality of life and reduce the risk of complications in type 2 DM patients.